Andy Warhol : Art and films. - Alloway, Lawrence; Battcock, Gregory; Blum, Irving; Bourdon, David; Brown, Tally; Carey, Ted; Castelli, Leo; Curtis, Jackie; Cutrone, Ronnie; Galster, Robert; Geldzahler, Henry; Gluck, Nathan; et al. (Ann Arbor : UMI Research Press, 1986)
What makes Andy Warhol tick ? What attraction did he hold for such Pop Luminaries as Edie Sedgwick, Candy Darling, Ingrid Superstar, and Pope Ondine ? Art historian Patrick Smith examines this elusive artist's work, his studio practices, and the mystique that has surrounded him and provides a fresh look at this ingamous Pop artist, who seems to delight in creating and passing along myths concerning his life and work. Based on extensive reseach and interviews with the "people who were there". as well as with Warhol himself, Andy Warhol's Art and Films contains new information about warhol and his work, and exposes some commonly-held misconceptions. Through a comprehensive analysis of Warhol's commercial work of the 1950s, Smith shows that Warhol used pop imagery much before his acclaimed "Pop" phase, and that his use of both paid and unpaid assistants began during the same time. Smith uses Warhol's obsession with stardom and fame as the basis for an examination of the Warhol Films, showing that the artist's fascination with glamour, even "seedy glamour", created an atmosphere where anyone could be a superstar : a transvestite, a poet, a debutante. Smith looks at this "desert of destroyed egos" and offers a penetrating portrait of Warhol, his work, his motives, and the frenetic aura that surrounded the "Factory"
Engels
boek
Keywords: Warhol, Andy